Correction method of the coloration in fluorescent nuclear track detector. (February 2023) - Kusumoto, Tamon; Akselrod, Mark S.; Harrison, Jonathan; Kodaira, Satoshi
Abstract: A fluorescent nuclear track detector (FNTD) is a single crystal of aluminum oxide doped with carbon and magnesium (Al2 O3 :C, Mg). We report calibration method of difference in the fluorescence intensity depending on the color center concentration (coloration) using a confocal microscope. The fluorescence intensity ratio of 510–530 nm due to the excitation at 488 nm to the reflection intensity of 483–493 nm is used for the coloration correction. The fluorescence track intensity of alpha particles increases monotonically with the color center concentration. From the relation between values of coloration concentration and the fluorescence track intensity of alpha particles, we have made a correction function. Consequently, the standard deviation of the detection of alpha particles with the coloration correction becomes six times smaller than without it. Additionally, the track response curve is properly made in a wide LET range from 1 to 200 keV/μm. Highlights: We have corrected the difference of the sensitivity between FNTD chips. The deviation becomes six times lower by the correction. The track response curve of FNTD is made in a wide LET range.